Performance evaluations of adaptive dynamic source routing protocol for mobile ad hoc network / Zuraida Abdullah Hani - Abdullah Hani, Zuraida (2007)
Mobile Ad Hoc Network (MANET) is a collection of wireless mobile nodes forming a temporary network without the use of any existing network infrastructure or centralized administration. The topology of the network is dynamic and the changes are often unpredictable. Nodes in ad hoc network find the routes themselves; thus, routing poses a big challenge. Many routing protocol had been proposed in literature. Dynamic Source Routing (DSR) protocol which is an on demand base routing, seems to have good performance and more reliable in dynamic environment. However the routing overhead of DSR needs to be improved. To overcome the weakness, instead of improving the features in the protocol, active source is introduced. This active source is an independent module and does not change any existing aspect of the DSR module. In active source, active packet is deployed. This active packet roams around the network and collects network topology information in its cache. By checking all the contents in active packet when it passes through networks nodes, route cache of network nodes is updates. In this research, both DSR and active source are implemented and combined in OPNET simulation software. The results show the deployment of this active source reduces up to 49 percent routing overhead and reduces end-to- end delay until 20.5 percent. The frequent update of route cache in network nodes, make network nodes always ready with valid route. These contributions improve the routing overhead and end-to-end delay.